EFEKTIVITAS SOCIAL MEDIA PADA TINGGINYA KENAIKAN PEMBELIAN ? - Melati Puspa Pramudita; Suharnomo Suharnomo (ITB AAS INDONESIA, 2023)
The use of the internet and digital devices that shot up high into the spotlight for businessmen. They are competing to market their products through the internet in order to increase sales. Buying interest by buyers or customers can be caused by many things, one of which is the first celebrity endorsement where currently many buyers are buying an item because their idol is promoting the item, the second is social media advertising where there are lots of online platforms used to promote an item. product, and the third is customer experience where the buyer will buy based on the experience of other buyers or he will buy again because of his own experience. Therefore, this study aims to determine the effect of celebrity endorsement, social media advertising, and customer experience on purchase intention. The results of this study are celebrity endorsement, social media advertising, and customer experience have an effect on purchase intention. Key Words : celebrity endorsement, social media advertising, customer experience, purchase intention